Running Dictation: an Effective Strategy for Teaching Vocabulary - Shafara, Inaya Zada; Zuhriyah, Mukminatus (Discovery, 2024)
The students’ less interest and motivation in learning vocabulary caused their poor vocabulary mastery. Therefore, the researchers were interested in conducting a pre-experimental study to know whether running dictation strategy was effective for teaching vocabulary. The population of this study was all the students of class VIII of MTs. Bahrul Ulum Genukwatu, Jombang. Then, the sample was 30 students of class VIII A. The instruments used to collect the data were pre- test and post-test of vocabulary. The students got the pre-test before the treatment conducted and the post-test after the treatment. After all the data from the pre-test and post-test were collected, the mean scores of the pre-test and post-test were calculated. It was followed by a paired-sample t- test calculation because their mean scores were different. The results showed that the mean score in the pre-test was 57 and the mean score of the post-test was 78. The sig. (2-tailed) score of the paired-sample t-test was 0.000. It means that the implementation of running dictation strategy was effective for teaching vocabulary. Thus, it is hoped that the results of this study can become a reference for the EFL teachers when teaching vocabulary.